Pemanfaatan Media Komunikasi dan Informasi dalam Perwujudan Pembangunan Nasional - Dharlinda Suri (Jurnal Komunikasi Pembangunan, 2019)
This scientific work is the result of the analysis and study of literature that reviews the communication and information media, namely social media in the form of social networks as a very effective medium used as a medium of communication and information to convey problems or aspirations of the community, especially for regions that have not been touched by the media optimally. widely known by the general public, especially officials who are currently serving. This study has a purpose for: first, to describe the characteristics of digital age society that uses communication media. Second, describing the linkages of the media of communication with national development and Third, describing the opportunities and challenges that arise in the digital era society. And fourth, describe the efforts that must be done in the digital era.This research method is a descriptive study with a qualitative approach. Researchers conduct data collection in accordance with existing events. Then the data is analyzed by means of data collection, data reduction, data presentation then drawing conclusions or verification. The results of the study show that national development will be well realized if there is a communication medium in the form of social networks that are used by the community correctly, ethically and can be accounted for. This can be reached in the wider community with the existence of cooperation between the community and the local government, namely by conducting counseling in all places evenly.